Engineering Microcapsules for Simultaneous Delivery of Combinational Therapeutics. Issue 11 (2nd September 2020) - Huang, Lu; Zhou, Jianhua; Chen, Yin; Li, Wei; Han, Xing; Wang, Liqiu
Abstract: The combination of chemo‐ and photothermal therapy is an effective strategy to improve clinical outcomes and minimize side effects. For simultaneously delivering chemo‐ and photothermal agents to the tumor region to exert their synergistic effect, an efficient and safe drug co‐delivery platform is in great need. Microcapsules (MCs) are promising drug carriers for local treatment of tumors. However, their applications in chemo‐photothermal combinational therapy have not been fully explored. Herein, novel doxorubicin (DOX) and indocyanine green (ICG)‐incorporated microcapsules (DIMCs) are reported for highly efficient delivery of combinational therapeutics. To obtain DIMCs with precise configuration and controlled drug release characteristics, the microfluidic double‐emulsion templating method is adopted and factors dominating the size and morphology of DIMCs are investigated. Under optimized conditions, DIMCs with well‐defined hydrogel cores and polymeric shells can be steadily prepared, which are hydrolytically degradable, allow for pH‐sensitive sustained release of the drug payload, and show excellent photothermal effects. The in vitro experiment shows that DIMCs exhibit significantly enhanced antitumor efficiency owing to the synergistic effects of chemo‐ and photothermal actives, showing great potential as a new therapeutic platform in local treatment of cancers. Abstract : A highly monodisperse and biodegradable core–shell microcapsule incorporated with chemo‐ and photothermal combinational therapeutics is prepared by microfluidic double‐emulsion templating method. It shows excellent biodegradability, well‐controlled drug release profiles, high photothermal efficiency, and enhanced therapeutic efficacy, which is promising for local combinational anticancer treatment.